A critical analysis of Islamic Equity Funds - Clarke, Kai A (2012)
This dissertation analyses the impact of using various Shari’ah screens on the FTSE 250 and deduces a suitable screening method. This index has therefore been selected as the asset universe. The dissertation has reviewed the methodologies of the most prominent funds and indices (5) in order to apply their apparent screening features to the asset universe. This research shows that the use of Shari’ah screens are inconsistent and consequently leads to selection differences in opinion when halal assets are chosen. Thus, the aim of this research is to construct a framework which leads to a standardized methodological approach for the selection of assets with respect to the Islamic principles that are defined by the sources of Shari’ah.